Acute and Subacute Toxicity of Rhamnus prinoides Leaves on Histopathology of Liver, Kidney, and Brain Tissues, and Biochemical Profile of Rats - Melese Shenkut Abebe (Journal of Toxicology)
Rhamnus prinoides is used as a traditional medicinal plant to treat pneumonia, sprain, gonorrhea, rheumatism, and ringworm infections as well as for the preparation of local beverages in Ethiopia. It has a widespread antioxidant, antimalarial, antimicrobial, wound healing, and anti-inflammatory activities. These activities are due to the presence of alkaloids, steroids, triterpenes, tannins, flavonoids, flavones, phenols, and glycosides. This study aimed to investigate acute and subacute toxicity of R. prinoides leaves on histopathology of the liver, kidney, and brain tissues, and biochemical profiles of rats. For the acute toxicity study, female rats were treated with R. prinoides at a dose of 5000 mg/kg body weight and followed-up for 14 days. In the subacute toxicity study, four groups of rats were used. The first three groups, respectively, received 250, 500, and 1000 mg/kg body weight of R. prinoides extract and the fourth group was a control group. Signs of toxicity, food intake, and weight was recorded. At necropsy, organ weight measurement and macroscopic and microscopic evaluations of the liver, kidney, and brain were carried out. Different clinical chemistry profiles of rats were also measured. Single-dose oral administration of R. prinoides extract at 5000 mg/kg produced no mortality indicating the LD50 is greater than 5000 mg/kg body weight. A four week administration of R. prinoides extract did not bring deleterious outcomes on the food consumption and weight gain of rats. Moreover, gross examination, histopathological evaluation, and weight measurement conducted on the liver, kidney, and brain did not reveal treatment related changes. The biochemical analysis showed no significant difference between the treatment and control groups. Consumption of R. prinoides leaf for 4 weeks might not have a toxic effect in rats. However, further investigations upon long-term administration should be conducted to have a wider safety margin.